2012
DOI: 10.1016/j.janxdis.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-compulsive disorder and comorbid depression: The role of OCD-related and non-specific factors

Abstract: Although comorbid depression is a predictor of poor treatment response in obsessive-compulsive disorder (OCD), there is limited understanding of factors that contribute to depression severity in OCD. The current study examines the influence of OCD-related factors (autogenous obsessions and obsessional beliefs) and non-specific factors (avoidance and anxiety) on depression severity in a sample of OCD patients. There were 56 participants with only OCD and 46 with OCD and comorbid depression. Self-report question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 72 publications
2
19
0
1
Order By: Relevance
“…Our initial analyses replicated the independent associations between adult OC symptoms and anger proneness, anger expression styles, depression, anxiety, family cohesion and family adaptability found in prior research (Whiteside and Abramowitz, 2004, 2005; Pens et al, 2012; Yap et al, 2012; Peris and Piacentini, 2013; Gorenstein et al, 2015; Murphy and Flessner, 2015; Nissen et al, 2016; Piacentino et al, 2016; Tellawi et al, 2016). …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our initial analyses replicated the independent associations between adult OC symptoms and anger proneness, anger expression styles, depression, anxiety, family cohesion and family adaptability found in prior research (Whiteside and Abramowitz, 2004, 2005; Pens et al, 2012; Yap et al, 2012; Peris and Piacentini, 2013; Gorenstein et al, 2015; Murphy and Flessner, 2015; Nissen et al, 2016; Piacentino et al, 2016; Tellawi et al, 2016). …”
Section: Discussionsupporting
confidence: 77%
“…Due to the correlational links between depression, anxiety and OC symptoms (Yap et al, 2012; Nissen et al, 2016), the inclusion of depressive and anxious symptoms in the moderation regressions provided a particularly stringent test of our models. Of note, even after accounting for current depression and anxiety, the moderating effects of anger suppression and anger proneness remained significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression symptoms may therefore occur as a reaction to the high levels of anxiety, functional impairment, and suffering associated with a severe chronic and incapacitating condition such as OCD. 37 Our study adds to the existing body of knowledge by revealing important data on the quality of life of adolescents with OCD, but some limitations should be taken into consideration while interpreting results. The fact that we used a population-based sample, on the one hand, is a strength of the study, but on the other it prevents our data from being extrapolated to other populations of outpatients or inpatients, with potentially more severe symptoms and, as a consequence, a poorer quality of life.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Quarantini et al (2011) found depression was associated with just four of six OC dimensions they investigated. Despite this variability, the high levels of comorbidity found in clinical populations and the moderate to strong inter-correlations between measures of MDD and OCD (van Oppen et al, 1995; Taylor, 1998; Yap et al, 2012) suggest a commonality.…”
Section: Introductionmentioning
confidence: 99%